PENUMBUHAN KREATIVITAS ANAK MELALUI APRESIASI SASTRA - Siti Anafiah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: Child literature is a useful reading for children. Through literature, children's creativity can grow and develop. With literature, children can also hone appreciation that is beneficial to the child. By reading literature, children can feel something fun and exciting. In addition, literary works also provide values and knowledge that has never been known by children. The child will be motivated to read, explore as he wishes, and can develop his imagination.